(untitled) (Journal of the College of Basic Education, 2022)
In this study, a new type of composite attapulgite-melamine- urea (AMU) has been synthesized. AMU has been characterized by FTIR. The new composite was used to adsorption Cr+6 from aqueous solution by conditions of PH, temperature, weight of adsorbent and contact time. It was found that the composite was effective in removing the Cr+6 at pH = 2, contact time (90 min) and temperature (25 ° C), weight of the adsorbent (2 gm). The results showed that the adsorption on the surface of AMU under go to Freundlich isotherm. Thermodynamic parameters (∆S°,∆H°,∆G°) have been calculated.